Design and fabrication of GPS bicycle tracking / Siti Nur Hanisah Noor Azmi and Hazim Sharudin - Noor Azmi, Siti Nur Hanisah; Sharudin, Hazim (School of Mechanical Engineering, 2023)
GPS Bicycle Tracking may be a device with a group of software that may help any bicycle owner to trace their bicycle easily by employing a gadget or mini wireless GPS itself. However, the foremost mentioned problem that has been waiting to be solved are renter information not systematic and losing track of your time using the bicycle. Therefore, the target of this project is to assist any bicycle owner or rental bicycle business owner to stay track of their bicycle. During this project, there'll be a design and fabricate process for the GPS tracking device. The device is going to be built by using Arduino Board. On the other hand, a range set of information from respondent and past project research are accustomed incorporate the software for tracking system. At the top of this project, it should achieve the target of the project and therefore the device is favorable for the cyclist, bicycle owner and bicycle rental business owner. Finally, this project represented a brand-new innovative side of GPS bicycle tracking systems by having a brand-new approach with having as much research because the reference of the project to form sure the project is successful.